AE Aquarii: A Short Review - P. J. Meintjes; A. Odendaal; H. van Heerden (Acta Polytechnica CTU Proceedings, 2015)
The nova-like variable AE Aquarii has been continuously studied since its discovery on photographic plates in 1934. In this short review the peculiar multi-wavelength properties of AE Aquarii will be reviewed and explained in context of its evolution from a high mass transfer phase, during which period it could have been a supersoft X-ray source (SSS).